Determination of Microbiological Quality of White Cheeses Marketed in Afyonkarahisar - Kara, Recep; Acaroz, Ulas; Gurler, Zeki; Zengin, Zeyneb Sadigzade; Soylu, Ali (International Journal of Sustainable Agricultural Research, 2020)
Cheese is a dairy product with a high nutritional value, a unique flavor, aroma, a long shelf life, and a very different variety. Cheese may be contaminated with harmful microorganisms which may pose a risk to public health during the raw material procurement and production stages. This study investigated the microbiological quality of 60 white cheese samples, marketed in Afyonkarahisar province. The mean levels of total mesophilic aerobic bacteria, Enterobacteriaceae, coliform, Esherichia coli, coagulase-positive staphylococci, and yeast-mold were determined as 2,1x105, 1,4x104, 2,1x103, 4,5x102, 4,1x102 and 3,8x103 CFU/g, respectively. Also, Escherichia coli was found in 10% (6/60) of the samples between the level of 102-105. Consequently, the microbiological quality was found to be insufficient in some of the samples examined. Therefore, it is recommended to take necessary hygienic measures in raw material supply. In addition, necessary precautions should be taken in all stages of cheese production and attention should be paid to the personnel and equipment hygiene.